Synthesis and Biosynthetic Trafficking of Membrane Lipids - Blom, Tomas (Cold Spring Harbor Laboratory Press, 2011)
Eukaryotic cells can synthesize thousands of different lipid molecules that are incorporated into their membranes. This involves the activity of hundreds of enzymes with the task of creating lipid diversity. In addition, there are several, typically redundant, mechanisms to transport lipids from their site of synthesis to other cellular membranes. Biosynthetic lipid transport helps to ensure that each cellular compartment will have its characteristic lipid composition that supports the functions of the associated proteins. In this article, we provide an overview of the biosynthesis of the major lipid constituents of cell membranes, that is, glycerophospholipids, sphingolipids, and sterols, and discuss the mechanisms by which these newly synthesized lipids are delivered to their target membranes.